Primerjalni vidiki dobre obravnave oseb v specializiranih institucijah v Evropi - Fabijan, Emanuela (Socialno delo, 2017)
"A comparative look on well-treatment of people in European specialised institutions" is the official title of an international Erasmus+ project, financed by the European Commission and involving one NGO and one educational institution from three countries: France (Reims), Portugal (Porto) and Slovenia (Ljubljana). The project will last for three year, its aim being to compare good practices from the field of caring for people with mental health issues and physical disabilities in the mentioned countries. The report describes the visit of all the partners that took place from the 18th to 22nd of Seprember 2017 in Reims, where the coordinator of the project is located: Regional Institute for Social Work of Champagne-Ardennes (IRTSCA). The report comprises observations by an assistent from the Faculty of Social Work, University of Ljubljana, and by the president, users, an expert worker and a volunteer from Društvo Altra, an NGO from Ljubljana working with people with mental disabilites.
Keywords: socialne storitve; deinstitucionalizacija; duševno zdravje; mental health; telesna oviranost; standard of living; kakovost življenja; Društvo Altra